Platelet-activating factor causes ventilation-perfusion mismatch in humans. - Rodriguez-Roisin, R (1994)
We hypothesized that platelet-activating factor (PAF), a potent inflammatory mediator, could induce gas exchange abnormalities in normal humans. To this end, the effect of aerosolized PAF (2 mg/ml solution; 24 micrograms) on ventilation-perfusion (VA/Q) relationships, hemodynamics, and resistance of the respiratory system was studied in 14 healthy, nonatopic, and nonsmoking individuals (23 +/- 1 [SEM]yr) before and at 2, 4, 6, 8, 15, and 45 min after inhalation, and compared to that of inhaled lyso-PAF in 10 other healthy individuals (24 +/- 2 yr). PAF induced, compared to lyso-PAF, immediate leukopenia (P < 0.001) followed by a rebound leukocytosis (P < 0.002), increased minute ventilation (P < 0.05) and resistance of the respiratory system (P < 0.01), and decreased systemic arterial pressure (P < 0.05). Similarly, compared to lyso-PAF, PaO2 showed a trend to fall (by 12.2 +/- 4.3 mmHg, mean +/- SEM maximum change from baseline), and arterial-alveolar O2 gradient increased (by 16.7 +/- 4.3 mmHg) (P < 0.02) after PAF, because of VA/Q mismatch: the dispersion of pulmonary blood flow and that of ventilation increased by 0.45 +/- 0.1 (P < 0.01) and 0.29 +/- 0.1 (P < 0.04), respectively. We conclude that in normal subjects, inhaled PAF results in considerable immediate VA/Q inequality and gas exchange impairment. These results reinforce the notion that PAF may play a major role as a mediator of inflammation in the human lung.